How to Write a Formula for a Recursive Sequence
A sequence in which the value of each statement is determined by the previous statement in the sequence is called a recursive sequence.
The formula of a recursive sequence is as follows:
\(a_n = f(a_{(n-1)})\), where a_n is the nth term of the sequence and \(a_{(n-1)}\) is the \((n-1)\)th term of the sequence. The function \(f(a_{(n-1)})\) is called the return relation and describes the relationship in the sequence.
Step-by-step to find the general formula for the recursive sequence
To find the general formula for the recursive sequence, follow the step-by-step guide below:
- Start by identifying the first few terms of the recursive sequence.
- Attempt to find a pattern in the terms, such as a specific difference or ratio between consecutive terms.
- Use the pattern identified in step 2 to express the nth term of the sequence in terms of the previous terms.
- Solve for the explicit formula using the recursive formula found in step 3 and the initial conditions of the sequence.
- Test the explicit formula using the first few terms of the sequence to confirm it is correct
- If the explicit formula does not match the initial terms, try to find a new pattern or check for errors in the previous steps.
Example: Find the general formula for the recursive sequence defined by the following:
a1 = 2 an = 3an-1 – 2
Step 1: Identify the first few terms of the sequence: a1 = 2 a2 = 3(a1) – 2 = 3(2) – 2 = 4 a3 = 3(a2) – 2 = 3(4) – 2 = 10 a4 = 3(a3) – 2 = 3(10) – 2 = 28
Step 2: Look for a pattern: We can see that the nth term is equal to 3 times the (n-1)th term minus 2.
Step 3: Express the nth term in terms of the previous terms: an = 3an-1 – 2
Step 4: Solve for the explicit formula using the recursive formula and initial conditions: We know that a1 = 2, so we can substitute that into the recursive formula: an = 3an-1 – 2 a1 = 2 a2 = 3(a1) – 2 = 3(2) – 2 = 4 a3 = 3(a2) – 2 = 3(4) – 2 = 10 a4 = 3(a3) – 2 = 3(10) – 2 = 28
From this, we can see that the explicit formula is: an = 3^n-1 * 2
Step 5: Test the explicit formula using the first few terms of the sequence: a1 = 2 = 3^(1-1) * 2 a2 = 4 = 3^(2-1) * 2 a3 = 10 = 3^(3-1) * 2 a4 = 28 = 3^(4-1) * 2
The explicit formula matches the initial terms of the sequence, so it is correct.
Related to This Article
More math articles
- Full-Length SSAT Middle Level Practice Test-Answers and Explanations
- What Are the Applications of the Law of Cosines?
- What is the Relationship Between Arcs and Central Angles?
- How to Find Values of Functions from Graphs?
- How Is the ALEKS Test Scored?
- What Kind of Math Is on the Accuplacer Next-Generation Test?
- Distinguishing Angles: Acute, Right, Obtuse, and Straight
- What does SAT Stand for?
- The Fundamental Theorem of Algebra
- The Ultimate SBAC Algebra 1 Course (+FREE Worksheets)
What people say about "How to Write a Formula for a Recursive Sequence - Effortless Math: We Help Students Learn to LOVE Mathematics"?
No one replied yet.